Effect of supplementation Herbal Methionine as substitute Synthetic Methionine in the quality characteristics of the eggs of Japanese Quail. - Hamodi, Sunbul J.; O. Al-Amidi, Haider F. (Journal of Kerbala for Agricultural Sciences, 2017)
This study was conducted at Babylon protectors, in al-mussaib, Babylon Governorate, from 18/3/2016 to 18/7/2016 to determine the effect of addition Herbal methionine and compared with DL-methionine in egg quality characteristics for Japanese quail. A total 240 females quail at 8 weeks of age, randomly divided into eight dietary treatment groups, each treatment was contained 3 replicates (ten females .replicate -1). The birds were fed on basic diet and then added herbal and synthetic methionine as follows: (T1) Control treatment (without supplementating of synthetic methionine). (T2) Diet supplementing 0.25 g dl- methionine /kg diet, (T3) Diet supplementing 0.5 g dl-methionine.kg-1 diet,(T4) Diet supplementing 0.75g dl-methionine .kg-1 diet, (T5) Control treatment (without supplementation of herbal methionine), (T6) Diet supplementing 0.25 g herbal methionine/kg diet, (T7) Diet supplementing 0. 50g herbal- methionine. kg-1 diet,(T8) Diet supplementing 0.75g herbal - methionine .kg -1diet, The result for the experiment indicated that interfere the source of methionine with the concentrations (0.5 and 0.75 g.kg-1 diet) recorded the best significant differences for most quality characteristics of the eggs, like: Shell weight, Shell thickness, Albumen high, Albumen weight, Yolk percentages, Yolk high, Yolk index, Yolk weight, Yolk diameter.